Use of marketing in social enterprises. (2016) - Satar, Mir Shahid; John, Shibu; Siraj, Sadaf
Social entrepreneurship is relatively a new concept within social sciences. Like the case with any newly emerging field, social entrepreneurship is confronting the challenges of justifying the use of new constructs and hence the challenge of generating new knowledge and insights. Till date, the field of social entrepreneurship has majorly been consented as a multidisciplinary approach to social problem solving. In this regard, researchers are attempting to take insights from different disciplines in an effort towards delimiting the scope and context of social entrepreneurship. However, social entrepreneurship is projected or seen as sharing much in common with business management and entrepreneurship. As such, the different approaches of management domain find high appropriateness for application, explanation and further expansion of this field. In light of the above and on the basis of a few qualitative case studies conducted in the western countries till date, the paper attempts to gain critical insights about the use of marketing concepts in social enterprises.